ANALISA HASIL UJI KEKUATAN TARIK, TEKAN & STRUKTUR MAKRO SAMPAH PLASTIK JENIS PET, HDPE, DAN CAMPURAN (PET+HDPE) - Ramagisandy, Holy; Siswanto, Rudi (JTAM ROTARY, 2021)
Plastik is a material which has difficult to decompose. Therefore, the utilization of waste into useful material is important to do. This study aims to identify the tensile strength, bending, and macro structure of recycled PET, HDPE, and PET + HDPE plastik waste mixtures and recommendations for plastik products that fit the characteristics of these plastik types. PET and HDPE plastik waste is melted with oil and reprinted into tensile and bending test samples in accordance with predetermined variations, and then the results of the fracture are analyzed in a macro structure. Based on tensile testing, the tensile strength test results have the highest stress and strain values obtained in the mixture of 40% + HDPE 60% (B2) used oil specimens of 10.58 MPa and strain values of 11.98%. The results of bending strength testing which has the highest bending stress value and maximum load value are obtained in plastik mixture specimens with 30% used oil mixture + 70% HDPE (B1) of 11.58 MPa and for maximum load values of 43.33 KN. Testing the tensile strength and bending strength of the type of plastik mixture Oil and HDPE + PET (50%: 50%), the results obtained can still not be recommended to be used as a paving block product because the value of stress, strain, bending stress, and the maximum load is still relatively low, namely for the tensile test the highest variation of stress value is 5.21 MPa, the highest variation of strain value is 5.23%, the maximum load value is 10 KN, and the highest variation of bending stress value is 40% + 60% by 4.01 MPa.